Toyin Falola@65 Conference: African Knowledge and Alternative Futures - Oluwatoyin Vincent Adepoju (Yoruba Studies Review)
A defining moment for me at the Toyin Falola@65 Conference titled “African Knowledges and Alternative Futures” that ran from the 29th to the 31st of January 2018 at the University of Ibadan, Nigeria, was the declaration at a paper presentation session by a scholar from a Nigerian university that the culture of making promotion of Nigerian academics dependent on publication in journals outside Nigeria, particularly from the West, is ultimately counterproductive to the development of a robust academic culture in Nigeria. “Do US or British academics, for example, have to publish in Nigerian journals?” he asked. This loaded question is at the heart of the challenges and paradoxes provoked by the conference. Another definitive encounter for me was another presenter’s outlining of the concept of an African, as different from an Asian or a Western epistemology or way of arriving at relating to knowledge. Yet another was Emmanuel Ofuasia’s explanation of what he describes as the Yoruba origin Ifa knowledge system’s anticipating of deconstructivist hermeneutics centuries before the development of this post-modern scholarly phenomenon in the West. Complementing these occurrences is yet another represented by Dr. Joan Ugo Mbagwu expounding on indigenous methods of conflict resolution and countering terrorism in Africa. I shall use these encounters as pivots in exploring the significance of the conference in the body of this essay.